META ANALISIS MODEL PROJECT BASED LEARNING TERHADAP KEMANDIRIAN BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Lestari, Nyoman Ayu Putri; Ni Ketut Suarni; I Gede Margunayasa (Program Studi Pendidikan Guru Sekolah Dasar-Universitas Muhammadiyah Kupang, 2024)
The learning model in the Independent Curriculum adopts various learning models, one of which is Project-Based Learning (PjBL), emphasizing project-based learning. However, the reality is that students' achievement in self-directed learning and critical thinking skills is still considered low. Therefore, it is hoped that the implementation of the PjBL learning model can enhance students' self-directed learning and critical thinking skills in education. Hence, this research aims to assess the impact of PjBL on students' self-directed learning and critical thinking skills. Through a descriptive research method, an analysis was conducted on 20 similar journals to evaluate the effects of implementing PjBL on students' self-directed learning and critical thinking skills. The analysis revealed an effect size value of 1.063, as per Cohen's interpretation table, confirming that the Project-Based Learning Model significantly influences the enhancement of students' self-directed learning and critical thinking skills in elementary school.